Taking Full Advantage of the COVID-19 Era to Intensify the Use of Information and Communication Technology Tools in Higher Education Institutes - Ohei, Kenneth Nwanua; Lubbe, Sam (International Review of Management and Marketing, 2022)
In the past, especially in underdeveloped countries, Information & Communication Technology (ICT) tools in higher education institutions were underutilized. But the unanticipated Coronavirus Disease 2019 (COVID-19) disaster, has forced everyone in the world to rely on ICT resources for education. This paper discusses the need to intensify the use of Information & Communication Technology (ICT) tools in higher education institutions by thoroughly exploiting the COVID-19 global state of emergency. The study assesses the value of Information & Communication Technology (ICT) resources in academic institutions. More so, the study goes into further detail about the contributions of Information & Communication Technology (ICT) resources in higher education institutions during the COVID-19 pandemic. In this study, a scoping review was chosen in selecting previous studies related to the field of current research. The findings of this study revealed that the applications of Information & Communication Technology (ICT) tools are essential for educational advancement; that it significantly accelerated education process during the pandemic. The study’s findings also revealed that there are several key factors that can help intensify the use of Information & Communication Technology (ICT) tools in higher education institutions.